DEVELOPMENT OF LEARNING MEDIA BASED ON ANIMATION VIDEO IN LEARNING HYDROCARBON MATERIAL AT GRADE XI SENIOR HIGH SCHOOL - Fahlevi, Najla Rizani; Muchtar, Zainuddin (FKIP USK, 2024)
The impact of technological developments in education on learning process is significant. To be effective and efficient, the learning process must be developed, implemented, analyzed, and monitored. There are several students find it difficult to understand the terms, theories, and structures of carbon chain structures until they make an error; students mark in hydrocarbon quiz, with 0% student that have mark up from 61 to 100. Majority of student have mark in range 31 to 40 (39%) and least in range 51 to 60 at 4%. Teaching the structure of the carbon chain requires clear visualization, which would be helped by the teacher's exposure. It needs a proper media for teaching and visualizing how the chain's structure are. This research uses the ADDIE development model. This research begins by analyzing the problems and limitations faced in learning chemistry. The quality of animated video learning media with an assessment percentage of 84% by media experts, 91% by material experts. Based on the results of a questionnaire for 30 students, the percentage of assessment based on responses was 91% in the very good category. Based on test results on 30 students, with tcountgreater than ttable; 22.75166617 greater than 2.045 with the Ha hypothesis accepted. Class XI SMA Class XI Animation Based Learning Videos are declared valid based on expert and practitioner assessments. The results of the experts' assessments consistently categorize the animated videos being developed. The general assessment of this video is very good and usable.